LAW ENFORCEMENT OF CRIMINAL ACTS IN THE MISUSE OF SUBSIDIZED SOLAR OIL IN INDONESIA - Putra, Reza Oktriananta Hadyan; Subekti; Suyono, Yoyok Ucuk (jfpublisher, 2023)
The Oil and Gas Law provides a legal basis for steps to renew and realign Oil and Gas business activities. In accordance with the Oil and Gas Law, Pertamina’s function is a business entity, as an operator, by implementing the applicable laws and regulations. The government has established a government agency which in conducting its functions, duties, and authorities is independent, called the regulatory agency for the supply and distribution of fuel which was formed based on Government Regulation Number 67 of 2002 and Presidential Decree Number 86 of 2002, which referred to Government Regulation. This research aims to improve the supervision of the distribution of subsidized oil. Pertamina has collaborated with the Indonesian National Police through Pertamina Joint Agreement Letter (SKB) andNational Police Headquarters No. Pol. KEP/34/VII/2004 and Number KPTS-035/C00000/2004-S0 concerning on the Security of Kerosene and Diesel Fuel. Based on research result, the law enforcement on criminal act in the misuse of the trading system of subsidized diesel by the Police through investigations and investigations with the conclusion that the fulfillment of the elements of the article referred to in Article 55 of the Oil and Gas Law. Based on the Oil and Gas Law, the subjects are people and business entities. It can be seen in CHAPTER XI regarding criminal provisions.